2018
DOI: 10.1007/s11144-018-1515-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low loading of yttrium on Ni-based layered double hydroxides in CO2 reforming of CH4

Abstract: Ni/Al/Mg layered double hydroxides (LDHs) modified with low loading of yttrium (0.2 and 0.4 wt%) were used in dry reforming of methane at 700 °C. Physicochemical characterization, such as: X-ray fluorescence, N2 sorption, X-ray diffraction, temperature programmed reduction in H2, temperature programmed desorption of CO2, H2 chemisorption, thermogravimetry analysis coupled by mass spectrometry and Raman spectroscopy, showed that the introduction of low loadings of yttrium lead to a smaller Niº crystallite size,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
4
10
0
Order By: Relevance
“…The calculated M 2+ /M 3+ atomic ratios were fairly close to those assumed during the materials synthesis, indicating that the composition of LDHs may be easily controlled as reported before [74]. There are no significant difference regarding to BET surface area and pore volume of Ni-containing double-layered hydroxides-derived catalyst when the loading of yttrium is low (≤0.4%) compared with Y-free sample, only the average pore size decreases as the increase of yttrium at low loading of yttrium [44,47]. As described in the section before, the structural parameters showed that the yttrium loading up to 2.0 wt.% could result in the introduction of this metal into the periclase-like structure.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…The calculated M 2+ /M 3+ atomic ratios were fairly close to those assumed during the materials synthesis, indicating that the composition of LDHs may be easily controlled as reported before [74]. There are no significant difference regarding to BET surface area and pore volume of Ni-containing double-layered hydroxides-derived catalyst when the loading of yttrium is low (≤0.4%) compared with Y-free sample, only the average pore size decreases as the increase of yttrium at low loading of yttrium [44,47]. As described in the section before, the structural parameters showed that the yttrium loading up to 2.0 wt.% could result in the introduction of this metal into the periclase-like structure.…”
Section: Resultssupporting
confidence: 81%
“…36.7, 43 and 62.5° are observed, which corresponds to mixed oxides obtained after thermal treatment of double-layered hydroxides [44,45,47]. Fig.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations